Tiktok Sebagai Arena Mobilisasi Politik Dalam Pemilu Indonesia - Yurni Jusiani; Dea Sadariah; Sinta Rahmawati; Sri Wahyuni (CV. ITTC INDONESIA, 2026)
The development of digital technology has transformed the political communication patterns of Indonesian society, particularly through the use of social media. TikTok has become a platform that plays a crucial role in the political communication process because it can present information concisely, engagingly, and easily understood by the younger generation. This study aims to analyze TikTok's role as an arena for political mobilization in the 2024 Indonesian General Election, particularly in shaping the political preferences and behavior of young voters. The method used is a qualitative research approach with a literature study through data collection from scientific journals, books, academic articles, and various previous studies relevant to digital politics, social media, voter behavior, and the 2024 General Election. The results show that TikTok functions not only as a political campaign medium but also as a space for political image formation, digital narrative construction, and mobilization of political support. Campaign strategies that utilize visual content, humor, music, and popular culture have proven effective in increasing emotional closeness between candidates and young voters. In addition to its positive impact in increasing public political participation, the use of TikTok also poses challenges in the form of simplification of political information, the formation of digital echo chambers, and the potential for manipulation of public opinion. Therefore, improving digital political literacy is crucial to support the quality of democracy in the digital era.